2016
DOI: 10.1002/lary.26001
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescription for acute rhinosinusitis: Emergency departments versus primary care providers

Abstract: 4. Laryngoscope, 126:2439-2444, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Our findings suggested that poor access may have a greater impact on ED use for ARS by Medicaid, rather than the quality of care they receive at PCP offices. Looking at more than 37 million PCP and ED visits for uncomplicated ARS, we also found no differences in antibiotic prescribing patterns between the outpatient PCP and ED settings, and likewise found no differences in prescribing patterns by insurance status, for pediatric and adult patients . These findings suggested that patients’ expectation for a specific treatment likely does not drive disparate ED utilization either for ARS.…”
Section: Introductionmentioning
confidence: 53%
“…Our findings suggested that poor access may have a greater impact on ED use for ARS by Medicaid, rather than the quality of care they receive at PCP offices. Looking at more than 37 million PCP and ED visits for uncomplicated ARS, we also found no differences in antibiotic prescribing patterns between the outpatient PCP and ED settings, and likewise found no differences in prescribing patterns by insurance status, for pediatric and adult patients . These findings suggested that patients’ expectation for a specific treatment likely does not drive disparate ED utilization either for ARS.…”
Section: Introductionmentioning
confidence: 53%
“…Acute and chronic rhinosinusitis are the most frequent diagnoses associated with antibiotic prescription at outpatient physician visits, 7,12 with nearly 60% of visits associated with rhinosinusitis resulting in prescription of an antibiotic. 13 We previously have found that the frequency of acute CRS exacerbations is significantly associated with decreased general health-related QoL in a manner independent of the direct effects of chronic sinonasal symptoms. 3 CRS-related systemic medication use therefore may be an important indicator of the QoL of CRS patients that can easily be queried and utilized in both the clinical and research settings.…”
Section: Introductionmentioning
confidence: 90%
“…Although the mainstay of CRS maintenance medical therapy consists of saline nasal irrigations and topical intranasal corticosteroids that target sinonasal inflammation, CRS exacerbations frequently are treated with systemic medications, including oral antibiotics and corticosteroids. Acute and chronic rhinosinusitis are the most frequent diagnoses associated with antibiotic prescription at outpatient physician visits, with nearly 60% of visits associated with rhinosinusitis resulting in prescription of an antibiotic . We previously have found that the frequency of acute CRS exacerbations is significantly associated with decreased general health‐related QoL in a manner independent of the direct effects of chronic sinonasal symptoms .…”
Section: Introductionmentioning
confidence: 99%
“…We previously have found that for uncomplicated acute rhinosinusitis (ARS)—a common condition with more than 20 million cases annually in the United States—patients with Medicaid or self‐pay insurance status disproportionately are more likely to present to an emergency department (ED) for ARS versus privately insured patients . Children and adults suffering from ARS may seek care at an ED or primary care provider (PCP); in both cases, over 50% of adult and pediatric ARS patients receive an antibiotic independent of insurance status . Children of lower socioeconomic status are at a higher risk for intracranial complications of ARS .…”
Section: Introductionmentioning
confidence: 99%
“…5 Children and adults suffering from ARS may seek care at an ED or primary care provider (PCP); in both cases, over 50% of adult and pediatric ARS patients receive an antibiotic independent of insurance status. 6 Children of lower socioeconomic status are at a higher risk for intracranial complications of ARS. 7 Also, like adults, pediatric patients with Medicaid/CHIP have been shown to have problems with access to both primary care and specialty care when compared to patients with private insurance.…”
Section: Introductionmentioning
confidence: 99%